PENGARUH MODEL PEMBELAJARAN 'COOPERATIVE SCRIPT' BERBANTU MEDIA BONEKA TANGAN BERSERI TERHADAP KETRAMPILAN BERBICARA SISWA - Ika Sang Hidayatul Hijriah (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2021)
This study aimed to determine the effect of cooperative script learning model assisted by serial hand puppet media on the speaking skills of fourth grade students in Kedungumpul Village. The research was experimental research with the type of pre-experimental design. The samples taken for this study were 16 fourth grade students, whereas the sampling technique used is purposive sampling. The data were collected by using performance method which were then analyzed by using non-parametric statistical methods, namely the Wilcoxon test with the help of the SPSS version 25 program.The results showed that the cooperative script model assisted by serial hand puppet media had an effect on the speaking skills of fourth grade students in Kedungumpul Village. This is evidenced by the Wilcoxon test results obtained which is Asymp. Sig. (2-tailed) worth 0.000. The results of the pretest and posttest scores increased in average values, from 47.00 in the pretest value to 61.31 in the posttest value. The value 0.000 is less than 0.05. This means that the cooperative script learning model assisted by serial hand puppet media has an effect on students' speaking skills.